Design and Implementation of a Virtual Laboratory for Machine Dynamics - Aziz, EL-Sayed S.; Esche, Sven K.; Chassapis, Constantin (International Journal of Online and Biomedical Engineering (iJOE), 2010)
Laboratory experiments are considered to be a crucial component of engineering and science curricula by all stakeholders in the education process. In traditional laboratories, students develop practical skills and become effective professionals. However, the major drawbacks of traditional laboratories are their high demand on resources, significant maintenance costs and the inability to delivery the laboratory content in distance education. Virtual laboratory experiments represent a valuable option for educational laboratories, due to their advantages over traditional hands-on as well as remote experiments, including the ease of reconfiguring the experimental system, the high flexibility in the input specifications, the possibility of conducting experiments using devices otherwise infeasible and the option of re-running experiments multiple times.In response to the need for developing laboratory resources that provide a practical experience to online engineering students, this paper describes a simulation-based virtual laboratory, which is used at Stevens Institute of Technology (SIT) in a junior-level course on mechanisms and machine dynamics as a compliment to experimental work in the traditional hands-on laboratory. This virtual laboratory system alleviates the space, time and cost constraints associated with traditional laboratories and serves as an efficient teaching aid. It conveys to the students practical issues associated with actual experiments and provides learning outcomes that are comparable to those of traditional physical laboratories. The students have the opportunity to explore a wide range of experimental configurations and parameters. In addition, the system includes a realistic rendering of the experimental setup and its components, thus providing the students with a strong feeling of immersion, as if they were performing an experiment in a traditional laboratory.